2001
DOI: 10.1128/jb.183.15.4599-4608.2001
|View full text |Cite
|
Sign up to set email alerts
|

Competence Repression under Oxygen Limitation through the Two-Component MicAB Signal-Transducing System in Streptococcus pneumoniae and Involvement of the PAS Domain of MicB

Abstract: In Streptococcus pneumoniae, a fermentative aerotolerant and catalase-deficient human pathogen, oxidases with molecular oxygen as substrate are important for virulence and for competence. The signal-transducing two-component systems CiaRH and ComDE mediate the response to oxygen, culminating in competence. In this work we show that the two-component MicAB system, whose MicB kinase carries a PAS domain, is also involved in competence repression under oxygen limitation. Autophosphorylation of recombinant MicB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 29 publications
1
90
1
Order By: Relevance
“…Nevertheless, the essential processes regulated by VicRK in these organisms remain unknown. Defects in morphology and cell wall synthesis, decreased competence, sensitivity to antibiotics and fatty acids, attenuated virulence, and defects in biofilm formation have been associated with null vicK mutants or conditional mutants under non-functional conditions for VicR (Martin et al, 1999;Echenique & Trombe, 2001;Kadioglu et al, 2003;Ng et al, 2004;Senadheera et al, 2005). Some of these phenotypes appear to be organism-specific; however, no studies on GAS VicRK have been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, the essential processes regulated by VicRK in these organisms remain unknown. Defects in morphology and cell wall synthesis, decreased competence, sensitivity to antibiotics and fatty acids, attenuated virulence, and defects in biofilm formation have been associated with null vicK mutants or conditional mutants under non-functional conditions for VicR (Martin et al, 1999;Echenique & Trombe, 2001;Kadioglu et al, 2003;Ng et al, 2004;Senadheera et al, 2005). Some of these phenotypes appear to be organism-specific; however, no studies on GAS VicRK have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…VicR is essential in Bacillus subtilis (Fabret & Hoch, 1998), Staphylococcus aureus (Martin et al, 1999) and Streptococcus pneumoniae (Lange et al, 1999;Throup et al, 2000), and vicR cannot be inactivated unless VicR is provided in trans to these organisms (Throup et al, 2000) or PcsB is constitutively expressed in S. pneumoniae (Ng et al, 2003). VicK is also essential in B. subtilis, but not in S. pneumoniae and Streptococcus mutans (Fabret & Hoch, 1998;Echenique & Trombe, 2001;Senadheera et al, 2005). Since an unconditional vicR mutant is not available, various strategies, including bioinformatics, construction of hybrid regulator, depletion and overexpression of VicRK, and vicK inactivation, have been used to identify putative targets of VicRK (Fukuchi et al, 2000;Howell et al, 2003;Ng et al, 2003;Durac & Msadek, 2004;Mohedano et al, 2005;Senadheera et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the YycG/YycF system have shown that it is involved in competence development and virulence in S. pneumoniae (10,42). In S. aureus, the YycG/YycF system is thought to play a role in membrane permeability, and a temperature-sensitive mutant of S. aureus yycF exhibited attenuated virulence in an in vivo model (27).…”
mentioning
confidence: 99%
“…One of the major effects of ciaRH mutations in Streptococcus pneumoniae occurs with competence development (8,10,23). Insertional inactivation of ciaR and ciaH results in derepression of competence both in aerobic and microaerobic cultures (7).…”
mentioning
confidence: 99%